"Even though they insult us, the delivery they give us is the greatest thing": a qualitative study contextualizing women's experiences with facility-based maternal health care in Ethiopia - Ashley Hagaman; Humberto Gonzalez Rodriguez; Clare Barrington; Kavita Singh; Abiy Seifu Estifanos; Dorka Woldesenbet Keraga; Abiyou Kiflie Alemayehu; Mehiret Abate; Befikadu Bitewulign; Pierre Barker; Hema Magge (BMC, 2022)
Abstract Background Globally, amidst increased utilization of facility-based maternal care services, there is continued need to better understand women's experience of care in places of birth. Quantitative surveys may not sufficiently characterize satisfaction with maternal healthcare (MHC) in local context, limiting their interpretation and applicability. The purpose of this study is to untangle how contextual and cultural expectations shape women's care experience and what women mean by satisfaction in two Ethiopian regions. Methods Health center and hospital childbirth care registries were used to identify and interview 41 women who had delivered a live newborn within a six-month period. We used a semi-structured interview guide informed by the Donabedian framework to elicit women's experiences with MHC and delivery, any prior delivery experiences, and recommendations to improve MHC. We used an inductive analytical approach to compare and contrast MHC processes, experiences, and satisfaction. Results Maternal and newborn survival and safety were central to women's descriptions of their MHC experiences. Women nearly exclusively described healthy and safe deliveries with healthy outcomes as 'satisfactory'. The texture behind this 'satisfaction', however, was shaped by what mothers bring to their delivery experiences, creating expectations from events including past births, experiences with antenatal care, and social and community influences. Secondary to the absence of adverse outcomes, health provider's interpersonal behaviors (e.g., supportive communication and behavioral demonstrations of commitment to their births) and the facility's amenities (e.g., bathing, cleaning, water, coffee, etc) enhanced women's experiences. Finally, at the social and community levels, we found that family support and material resources may significantly buffer against negative experiences and facilitate women's overall satisfaction, even in the context of poor-quality facilities and limited resources. Conclusion Our findings highlight the importance of understanding contextual factors including past experiences, expectations, and social support that influence perceived quality of MHC and the agency a woman has to negotiate her care experience. Our finding that newborn and maternal survival primarily drove women's satisfaction suggests that quantitative assessments conducted shortly following delivery may be overly influenced by these outcomes and not fully capture the complexity of women's care experience.